Development and Validation of an Electronic Frailty Index Using Routine Electronic Health Records: An Observational Study From a General Hospital in China - Liang, Yao-Dan; Xie, Yi-Bo; Du, Ming-Hui; Shi, Jing; Yang, Jie-Fu; Wang, Hua (Frontiers in Medicine, 2021)
Background: This study aimed to develop and validate an electronic frailty index (eFI) based on routine electronic health records (EHR) for older adult inpatients and to analyze the correlations between frailty and hospitalized events and costs. Methods: We created an eFI from routine EHR and validated the effectiveness by the consistency of the comprehensive geriatric assessment-frailty index (CGA-FI) with an independent prospective cohort. Then, we analyzed the correlations between frailty and hospitalized events and costs by regressions. Results: During the study period, 49,226 inpatients were included in the analysis, 42,821 (87.0%) of which had enough data to calculate an eFI. A strong correlation between the CGA-FI and eFI was shown in the validation cohort of 685 subjects (Pearson’s r=0.716, P<0.001). The sensitivity and specificity for an eFI≥0.15, the upper tertile, to identify frailty, defined as a CGA-FI≥0.25, were 64.8% and 88.7%, respectively. After adjusting for age, sex, and operation, an eFI≥0.15 showed an independent association with long hospital stay (odds ratio [OR] =2.889, P<0.001) and death in hospital (OR=19.97, P<0.001). Moreover, eFI values (per 0.1) were positively associated with total costs (β=0.453, P<0.001), examination costs (β=0.269, P<0.001), treatment costs (β=0.414, P<0.001), nursing costs (β=0.381, P<0.001), pharmacy costs (β=0.524, P<0.001), and material costs (β=0.578, P<0.001) after adjusting aforementioned factors. Conclusions: We successfully developed an effective eFI from routine EHR from a general hospital in China. Frailty is an independent risk factor for long hospital stay and death in hospital. As the degree of frailty increases, the hospitalized costs increase accordingly.